The discharge capacity and design of curb inlets with and without clogging - Dube, Ntombikayise (My University, 2019)
Prolonged surface runoff on streets contributes to flooding, thus compromising the structural integrity of roads, increasing the probability of accidents and traffic stagnation, and as such drainage structures such as the Pretoria type curb inlet are integrated into the road infrastructure to facilitate conveyance of surface runoff into conduits. The Pretoria type inlet is popular in South Africa, but there is limited literature on its hydraulic performance. Therefore, this research is aimed at expanding the existing literature by assessing the behavior of the Pretoria type curb inlet and, developing design tools. Various configurations of the model of the Pretoria type curb inlet were fabricated in the Hydraulics laboratory of the School of Civil and Environmental Engineering at Witwatersrand University, and tests were carried out in a flume that simulated flow on the roadway with model a curb inlet that intercepted a portion of the flow. The tests were carried out on three longitudinal slopes of 0.25%, 0.5% and 0.75%, two cross-section slopes of 2% and 3%, with an undepressed and depressed gutter, and the mouth of the inlet free from any clog material and with clog material. To confirm the uniqueness of the Pretoria type curb inlet, we found that the Hydraulic Engineering Circular No. 22 (HEC-22) and Izzard methods did not give good prediction of the discharge capacity of the Pretoria type curb inlet. In contrast to previous work on the Pretoria type curb inlet which was restricted to 80% and 100% interception, this study explores a wider a range of interception efficiencies which make it more useful for design. Further, this work is the first known research investigation in South Africa that examines the influence of clogging on the performance of the Pretoria type curb inlet. We found that the discharge capacity of the curb inlet increases with the length of the opening, and an upstream transition section improves its efficiency. The efficiency of the inlet favors steep crosssectional slopes and gentle longitudinal slopes; depression of the gutter enhances the interception efficiency and this supports why the Pretoria type curb inlet is now synonymous with the depressed gutter. The reduced performance of the inlet due to clogging calls for concerted efforts at better solid waste management in South Africa.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering, 2019
Keywords: Filters and filtration; Shock waves